On the identity and status of Darala lineosa (Lepidoptera: Eupterotidae) - Prins, Willy De (Zootaxa, 2017)
In 1862, F. Walker described Darala lineosa in the family Liparidae (now Erebidae, subfamily Lymantriinae) on a single female (he stated that it is a male but see Swinhoe 1892: 209) from Australia (Walker 1862: 269). The genus Darala is now considered a synonym of the large genus Anthela which belongs to the Anthelidae, a family entirely confined to the Australian region with representatives in Australia and New Guinea (Edwards & Fairey 1996: 258). These authors mention 61 Anthela species with about the same amount of synonymic species-group names, but they do not cite Darala lineosa, already indicating that this species does not belong to the Australian fauna and hence that the indication of “Australia” in the original description, and repeated in Walker (1865: 369), is erroneous.